(untitled) (Journal of Foreign Language Studies, 2024)
Praxématique, first appeared in the 1970s in France, is a unique linguistic theory with many new points relating to the semantic relations between meanings expressed by language and objective reality, between reality and symbols of reality formed by language, and the adjusting roles of the society, of speaker in creating meanings. The applications of praxématique are also popular in different fields, such as the study on denomination, representation and translation… This article aims to discuss basic arguments of this theory and provide some application directions.